THE PHENOMENON OF EXPRESSIONISM IN GENETIC-TYPOLOGICAL DIMENSIONS OF WORLD AND NATIONAL LITERARY PROCESS - Lys, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the problem of expressionism establishing as art movement is considered, its philosophical base and historical background of formation are revealed, the main features of West-European invariant of expressionism are singled out, the perspectives of genetic-typological study of its Ukrainian invariant are found.